2022
DOI: 10.1073/pnas.2114064119
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting breakdown in nonhost effector–target interactions to boost host disease resistance

Abstract: Plants are resistant to most microbial species due to nonhost resistance (NHR), providing broad-spectrum and durable immunity. However, the molecular components contributing to NHR are poorly characterised. We address the question of whether failure of pathogen effectors to manipulate nonhost plants plays a critical role in NHR. RxLR (Arg-any amino acid-Leu-Arg) effectors from two oomycete pathogens, Phytophthora infestans and Hyaloperonospora arabidopsidis , enhanced pathogen infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…Viewed from the pathogen perspective, the failure of Pst urediniospores infection of barberry is mainly due to the inability of secreted effectors to modulate or suppress host defense factors. For example, the majority of the Phytophthora infestans effectors are not able to recognize the Arabidopsis proteins homologous to the corresponding targets of effectors in the potato host (McLellan et al ., 2022). TaSIG is a wheat susceptibility factor, which is presents only in monocot plants.…”
Section: Discussionmentioning
confidence: 99%
“…Viewed from the pathogen perspective, the failure of Pst urediniospores infection of barberry is mainly due to the inability of secreted effectors to modulate or suppress host defense factors. For example, the majority of the Phytophthora infestans effectors are not able to recognize the Arabidopsis proteins homologous to the corresponding targets of effectors in the potato host (McLellan et al ., 2022). TaSIG is a wheat susceptibility factor, which is presents only in monocot plants.…”
Section: Discussionmentioning
confidence: 99%
“…7). Our result is consistent with a recent study that demonstrated that AtPUB33 is a positive regulator of plant immunity, and expression of this gene reduces P. infestans colonization of host plants (McLellan et al ., 2022). However, further investigation is required to determine the substrate of NbPUB33 ubiquitination and to determine the role of NbPUB33 in promoting plant immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The RXLR effector Pi06099 from P. infestans is nucleo-cytoplasmically localized and promotes pathogen colonization [ 101 ]. Pi06099 interacts with the RL receptor phyB from both Arabidopsis and potato in Y2H and by CoIP ( Figure 2 ) [ 99 ]. Nothing further is known about how this interaction affects RL signaling, although phyB mutant plants are more susceptible to a variety of pathogens and display reduced SA and JA signaling [ 113 ].…”
Section: Light Signaling and Organelles Targeted By Pathogensmentioning
confidence: 99%
“…More recently, it was demonstrated that the perception of BL by StPhot1 suppresses plant defenses and also enhances StNRL1’s ability to target SWAP70 for degradation [ 75 ]. Moreover, Pi02860 also interacts with 14-3-3 phosphobinding proteins in potato and Arabidopsis ( Figure 2 ) [ 99 ]. The 14-3-3 proteins may have many pleiotropic functions but also interact with NRL proteins to modulate their activity following BL perception [ 98 ].…”
Section: Light Signaling and Organelles Targeted By Pathogensmentioning
confidence: 99%